Ethnic differences in risk factors and prevalence of type 2 diabetes in the adult population of the Russian Federation - I. V. Kononenko; M. V. Shestakova; A. R. Elfimova; I. A. Khomyakova; A. P. Buzhilova; N. G. Mokrysheva (Сахарный диабет)
BACKGROUND: Russia is one of the most multinational states in the world. Identification of ethnic groups with a higher risk of developing DM2, analysis of risk factors for the development of DM2 will allow developing personalized approaches to the prevention and treatment of DM2.AIMS: To reveal ethnic features of the prevalence of carbohydrate metabolism disorders and risk factors for the development of DM2 in the adult population of the Russian Federation.MATERIALS AND METHODS. A retrospective analysis of the database of the national epidemiological cross-sectional study NATION was carried out. Depending on the self-specified nationality, on the basis of anthropological characteristics, the following ethnic groups were identified: “Mongoloid population”, “Peoples of the Volga region”, “Peoples of the North Caucasus”, “Peoples of Transcaucasia”, “Russians”. The analysis consisted of several stages and included: analysis of the anthropometric features of the selected groups, taking into account the presence of carbohydrate metabolism disorders (MO); study of the prevalence of violations of the MA in the selected ethnic groups; analysis of ethnic characteristics of risk factors for the development of type 2 diabetes; analysis of the frequency of violations of the MA in various ethnic groups, taking into account the territory of residence. MR disorders were defined as the presence of DM and/or prediabetes. In accordance with the WHO criteria, HbA1c≥6.5% corresponded to the diagnosis of DM, HbA1c values in the range of 5.7%≤HbA1c<6.5% to the diagnosis of prediabetes.RESULTS: The highest frequency of violations of the MA was observed in the group «Peoples of the Volga region» (31.2%), the lowest in the «Peoples of the North Caucasus» (15.6%). BMI in the group “Peoples of the Volga region” was significantly lower than in the group “Peoples of the North Caucasus. Violations of MR were more often observed in the abdominal nature of obesity, obesity of the 1st stage, age over 45 years in the groups «Mongoloid population» and «Peoples of the Volga region» than in the peoples of the «Northern Caucasus» and «Transcaucasia». The frequency of occurrence of SR violations among representatives of the Volga Peoples group living in their historical territories was higher than among Russians living in the same regions: 32.5% and 24.3% (p<0.001 χ2 criterion), and also higher than in the Russian CFD: 32.5% and 27.4%, respectively, p=0.001 (χ2 test). The prevalence of violations of the MA among the peoples of the North Caucasus was less than among the Russians of the Central Federal District — 13.9% and 27.36%, respectively (p<0.001 χ2 criterion). The prevalence of MR violations among representatives of the “Peoples of the North Caucasus” group living in their historical territories (n=598) was less than among those living in other regions of the Russian Federation (n=164) (13.9% and 21.95%, p= 0.012 criterion χ2).CONCLUSION: In the present work, for the first time, we analyzed the prevalence of MR disorders in various ethnic groups of the population of the Russian Federation, identified certain ethnic characteristics of DM2 risk factors and their contribution to the development of the disease. The obtained results should be used for planning preventive programs in various regions of the Russian Federation.